THE APPLICATION OF PROBLEM SOLVING LERANING MODEL TO INCREASE CRITICAL THINKING ABILITY AND LEARNING OUTCOMES OF STUDENTS (The Study of Sains subject at fifth grade students of Elementary School 24 Bengkulu City ) - Era Putri Dewi Handayani; Wasidi Wasidi (DIADIK, 2019)
The main objective of this research was applicated Problem Solving Learning Model toincrease critical thinking ability and learning outcomes of students on Sains subject at fifth grade students of SD Negeri 24 Bengkulu City. This research method was class room action research (CAR) and experiment. The research conducted in three cycles; there were planing, action, observation, and reflexion. The subject of this research was fifth grade students of SD Negeri 24 Bengkulu City in academic years 2018/2019, on Sains subject which were consist of 32 students. There were 12 male and 20 female. Instrument of this research were observation sheet and test in the form analize data. In analizing data, the research use data collecting technique, quantitative, and qualitative approach. In conlusion, using Problem Solving Learning Model can increase critical thinking ability and learning outcomes of students on Sains subject, especially fifth grade students of SD Negeri 24 Bengkulu City